An ion diode with external magnetic insulation - Lopatin V. S.; Remnev G. E. Gennady Efimovich; Furman E. G. Edwin Gugovich; Makeyev V. A.; Stepanov A. V. Andrey Vladimirovich (2004, 2004)
Title screen